Effects of a Programme Integrating Multidisciplinary Approach and Self-Management on Chronic Kidney Disease Patients with Complications - Chosivasakul, Kullapungha; Piaseu, Noppawan; Sakdanupab, Surawit (Journal of Thailand Nursing and Midwifery Council, 2018)
Objective: To examine the effects of a program integrating multidisciplinary care with self-management in chronic kidney disease patients with complications. Design: One-group quasi-experimental research with a pre-test and a post-test. Methodology: Through simple random sampling (lot drawing), the sample consisted of 38 stage-III chronic kidney disease patients at the renal clinic of a hospital in Kanchanaburi province. The patients participated in a 12-week programme that integrated self-management concept, multidisciplinary care, and advanced practice nurses’ competency. This integrative approach was conducted to comprehensively assess health problems, promote coordination, introduce changes, organise empirical-knowledge-based educational activities, held experience-sharing sessions based on case studies, provide reﬂective thinking, perform telephone-counselling services, and pay home visits to encourage individual empowerment. The data-collecting instruments were 3 interview forms and records of clinical outcome assessment. The 3 interview forms were used to collect the participants’ (i) personal information; (ii) knowledge of chronic kidney diseases; and (iii) self-management behaviour. The records of clinical outcome assessment provided the participant’s health data, namely, their body mass index (BMI), systolic and diastolic blood pressure (SBP and DBP), Hemoglobin A1 (HbA1C), and Estimated Glomerular Filtration Rates (eGFR). The data were analysed using descriptive statistics, Wilcoxon signed-rank test, and One-way ANOVA with repeated measures. Results: After the programme, the patients’ mean scores on knowledge and selfmanagement (13.76 ±0.68 and 112.47 ±5.19) were signifcantly higher than before the programme. Regarding the patients’ clinical outcomes, their SBP, DBP, and HbAIC, were also signifcantly lower, with signifcant improvement in their eGFR. However, no signifcant change was found between the participants’ pre-experimental and post-experimental BMIs. Recommendations: It is recommended that advanced practice nurses monitor patients’ clinical outcomes by coordinating with a multidisciplinary team, to ensure appropriate provision of long-term care for each patient.